Localization of Neuronal Gain Control in the Pupillary Response - Carle, Corinne Frances; James, Andrew Charles; Rosli, Yanti; Maddess, Ted (Frontiers in Neurology, 2019)
Multifocal pupillographic objective perimetry (mfPOP) is being developed as an alternative to standard visual perimetry. In mfPOP, pupil responses to sparse multifocal luminance stimuli are extracted from the overall composite response. These individual test-region responses are subject to gain-control which is dependent on the temporal and spatial density of stimuli. This study aimed to localize this gain within the pupil pathway. Pupil constriction amplitudes of 8 subjects (41.5 ±12.7 y, 4 male) were measured using a series of 14 mfPOP stimulus variants. The temporal density of stimulus signal at the levels of retina, pretectal olivary nuclei (PON), and Edinger-Westphal nuclei (EWN) were controlled using a combination of manipulation of the mean interval between stimulus presentations (3 or 6 stimuli/s/hemiretina) and the restriction of stimuli to specific subsets of the 24 visual field test-regions per eye (left or right eye, left or right hemifield, or nasal or temporal hemifield). No significant difference was observed between mfPOP variants with differing signal density at the retina or PON but matched density at the other levels. In contrast, where signal density differed at the EWN but was the same at the retinal and PON levels e.g. between 3 stim/s homonymous hemifield and all test-region variants, significant reductions in constriction amplitudes were observed (t(30)= -2.07 to -2.50, all p<0.05). Similar, although more variable, relationships were seen using nasal and temporal hemifield stimuli. Results suggest that the majority of gain-control in the subcortical pupillary pathway occurs at the level of the EWN.